Mandatory Portfolio Disclosure, Stock Liquidity, and Mutual Fund Performance - AGARWAL, VIKAS; MULLALLY, KEVIN A.; TANG, YUEHUA; YANG, BAOZHONG (The Journal of finance (New York), 2015)
We examine the impact of mandatory portfolio disclosure by mutual funds on stock liquidity and fund performance. We develop a model of informed trading with disclosure and test its predictions using the May 2004 SEC regulation requiring more frequent disclosure. Stocks with higher fund ownership, especially those held by more informed funds or subject to greater information asymmetry, experience larger increases in liquidity after the regulation change. More informed funds, especially those holding stocks with greater information asymmetry, experience greater performance deterioration after the regulation change. Overall, mandatory disclosure improves stock liquidity but imposes costs on informed investors.